Pengaruh Permintaan Cabai Merah Terhadap Pendapatan Kelompok Tani Cabai Di Kabupaten Labuhanbatu - Anoviansyah, Yoan; Sepriani, Yusmaidar; Sarkum, Sumitro (LPPM Universitas Malikussaleh - Indonesia, 2018)
The purpose of this study was to determine the effect of demand for red chili (annum L capsicum) on farmer group income. The basis of the research was carried out by fluctuations in the price of red chili caused by the large number of offers and the large number of requests. This research was conducted in Labuhanbatu District, in Wonosari Neighborhood, Aek Paing Village, North Rantau District, Labuhanbatu Regency, North Sumatera Province. The number of samples used was 30 respondents as users of red chili. The results of this study by conducting data testing using SPSS 20.0 can be concluded that from the calculation of regression which states that the income of farmers group of chili heavily very influential on consumer demand in the village of Aek Paing, so that existing chili farmers can increase the production capacity of chili which is good to meet the needs of the community in the village of Aek Paing. This shows a very strong and positive degree because the value is in the number 0.9 close to 1 this means very strong influence the demand for the farmer group's income. Where as with the value of R square of 0.988, this means that the effect of variables X1- X3 simultaneously (simultaneously) to variable Y of 98.8%. The income variable of farmers in the Wonosari neighborhood of Aek Paing Sub-district of Labuhanbatu Regency is influenced by the demand varieties of red chilli, while the remaining 1.02 percent is influenced by other variables outside the model.